(untitled) (Książnica Śląska, 2025)
This article presents a regional bibliography and its workshop in several areas of contemporary librarianship. It serves as a source of inspiration for other library systems, including digital libraries, particularly in the context of full-text search capabilities, thanks to its ability to describe informational components. Bibliographic compilations represent a valuable information resource, carefully selected in terms of territory, time, and subject matter, and are readily published by online services. Bibliographies can also be integrated into extensive information systems, as illustrated by the example of the regional information cluster „Ariadna” at the Silesian Library. In the perspective of creating modern library systems, it can potentially serve as an information metasystem, as illustrated by the bibliographic service of North Rhine-Westphalia.